Rubidium Chloride Targets Jnk/p38-Mediated NF-κB Activation to Attenuate Osteoclastogenesis and Facilitate Osteoblastogenesis - Ouyang, Zhengxiao; Huang, Qianli; Liu, Bin; Wu, Hong; Liu, Tang; Liu, Yong (Frontiers in Pharmacology, 2019)
The unbalanced crosstalk between osteoclasts and osteoblasts could lead to the disruptive bone homeostasis. Herein, we investigated the therapeutic effects of rubidium chloride (RbCl) on ovariectomized (OVX) and Titanium (Ti) particle-induced calvaria osteolysis mouse models, showing that non-toxic RbCl attenuated RANKL-stimulated osteoclast formation and functionality, while significantly enhancing osteogenesis in vitro. The expressions of osteoclast-specific genes were down-regulated considerably by RbCl. Besides, despite the direct inhibition of RANKL-induced activation of MAPK signaling, RbCl was able to target NF-κB directly and indirectly. We found that after the co-stimulation of the c-Jun N-terminal kinase (Jnk)/p38 activator and RANKL, RbCl inhibited the elevated expression of p-IKKα and the degradation of IκBα in osteoclast precursors, indicating indirect NF-κB inhibition via MAPK suppression. Furthermore, the two animal models demonstrated that RbCl attenuated tartrate-resistant acid phosphate (TRAP)-positive osteoclastogenesis and rescued bone loss caused by hormonal dysfunction and wear particle in vivo. Taken together, these findings suggest that RbCl can target Jnk/p38-mediated NF-κB activation to attenuate osteoclastogenesis, while facilitating osteoblastogenesis both in vivo and in vitro, suggesting the possible future use of RbCl for surface coating of orthopaedic implant biomaterials to protect against osteoporosis.